Health promotion theory-based educational interventions for improving oral health in children and adolescents: a systematic review and meta-analysis - Abouzar Nazari; Mina Hajihashemi; Seyyed Roghayeh Safavi; Raziyeh Ataei; Maede Hosseinnia (BMC Oral Health)
Abstract Background Oral health is a crucial component of overall well-being, particularly in childhood and adolescence when lifetime habits are established. Health education and theory-Based health promotion interventions can enhance oral health outcomes more effectively than traditional knowledge-transfer methods. Objective The present systematic review and meta-analysis were performed with the objective of assessing the effectiveness of theory-Based health education and promotion interventions in impacting oral health outcomes among children and adolescents. Methods Based on PRISMA and PROSPERO registration, the systematic search in seven databases was performed up to March 2025. Only RCTs involving participants aged 5 to 18 years old and with use of theoretical models like the Health Belief Model, Theory of Planned Behavior, or Social Cognitive Theory were taken into account. Primary outcomes included oral health behavior, knowledge, attitudes, self-efficacy, and clinical indicators like dental plaque, periodontal status, and DMFT. The data were combined through random-effects meta-analysis, and risk of bias was assessed using the Cochrane RoB 2.0 tool. Results Nineteen RCTs were included. Interventions had a significant boost in self-efficacy (SMD = 1.49, 95% CI: 0.99,2.00), oral health-related quality of life (SMD = 7.38, 95% CI: 5.57,9.19), knowledge (SMD = 1.09, 95% CI: 0.80,1.39), attitudes (SMD = 9.32, 95% CI: 7.08,11.55), and behavior (SMD = 2.58, 95% CI: 2.03,3.12). Significant declines in dental plaque (SMD = -1.92, 95% CI: -2.42,-1.42) and periodontal health (SMD = -1.18, 95% CI: -1.83,-0.53) but not in DMFT scores (SMD = -0.11, 95% CI: -0.27,0.04) also occurred. High heterogeneity and small sample of evidence of publication bias were detected. Conclusions Theory-Based health education and promotion interventions are effective in enhancing oral health outcomes across a wide range of outcomes in children and adolescents. Future research should have long-term follow-up, standardization of outcomes measures, fidelity of intervention, economic evaluations, and equitable provision across diverse populations. Clinical trial number Not applicable. Trial registration This systematic review has been registered prospectively in PROSPERO (International Prospective Register of Systematic Reviews) with registration number CRD420251026862.